Training and Assistance in using the Canva application at SMP Muhammadiyah Ahmad Dahlan Metro - Angelica, Sabilla; Rahmadani, Ivonne Novenska; Yantika, Yuli; Rohmani (Jurnal Abdimas Nusantara, 2024)
At SMP Muhammadiyah Ahmad Dahlan Metro, learning and support in using the Canva application is intended to improve students' graphic design skills while encouraging the growth of their creativity and digital literacy. Through the stages of planning, teaching, and weekly mentoring, these activities are carried out in an organized manner and combine interactive techniques such as individual exercises, group discussions, and individual mentoring. An introduction to the Canva app, Canva features, and basic design methods such as choosing a template, adding graphic elements, and creating layouts are all covered in the training materials. The results of this activity show that students can create various imaginative designs, such as posters and visual aids for educational purposes. In addition to increasing technical proficiency, this program fosters teamwork, critical thinking, and the courage to experiment. However, a number of difficulties were discovered, including disparities in students' technical abilities as well as device and internet connection problems. Overall, this program has succeeded in encouraging students to utilize technology, fostering digital literacy in line with the demands of 21st century education, and equipping them to meet the demands of the workplace and classrooms of the future.